2006
DOI: 10.1364/oe.14.011442
|View full text |Cite
|
Sign up to set email alerts
|

Looking into the volcano with a Mid-IR DFB diode laser and Cavity Enhanced Absorption Spectroscopy

Abstract: We report on the first application of extended-wavelength DFB diode lasers to Cavity-Enhanced Absorption Spectroscopy in-situ trace measurements on geothermal gases. The emission from the most active fumarole at the Solfatara volcano near Naples (Italy) was probed for the presence of CO and CH(4). After passing through a gas dryer and cooler, the volcanic gas flow (98% CO(2)) was analysed in real time for the concentration of these species, whose relatively strong absorption lines could be monitored simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…A variety of atmospheric trace constituents have been successfully detected in the field using laser-based cavity ringdown (CRD) spectroscopy [4][5][6][7]. Most CRD field instruments extract atmospheric samples [8][9][10][11][12][13], and only a few have employed an open-path configuration [14,15]. For instruments using gas extraction, inlet losses of the target species must be established in independent measurements [16].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of atmospheric trace constituents have been successfully detected in the field using laser-based cavity ringdown (CRD) spectroscopy [4][5][6][7]. Most CRD field instruments extract atmospheric samples [8][9][10][11][12][13], and only a few have employed an open-path configuration [14,15]. For instruments using gas extraction, inlet losses of the target species must be established in independent measurements [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that this technique is compatible with different kinds of semiconductor lasers. Indeed, while OF-CEAS was previously developed in the NIR with distributed feedback telecom diode lasers (Morville et al, 2005;Kassi et al, 2006), it has been demonstrated that it is compatible with extended cavity diode lasers that operate in the visible (Courtillot et al, 2006;Horstjann et al, 2014) and with quantum cascade lasers (Maisons et al, 2010;Gorrotxategi-Carbajo et al, 2013) as well as more recently with interband cascade lasers (Manfred et al, 2015;Richard et al, 2016) in the mid-infrared region.…”
Section: Discussionmentioning
confidence: 99%
“…The laser spectroscopy technique going under the name of OF-CEAS was introduced by Morville et al (2005) and has been further detailed in different publications (Kerstel et al, 2006;Kassi et al, 2006;Ventrillard-Courtillot et al, 2009;Faïn et al, 2014;Maignan et al, 2014;Morville et al, 2014).…”
Section: Optical-feedback Cavity-enhanced Absorption Spectrometermentioning
confidence: 99%
See 2 more Smart Citations